2020
DOI: 10.3233/bmr-181308
|View full text |Cite
|
Sign up to set email alerts
|

Electromyography activities in patients with lower lumbar disc herniation

Abstract: BACKGROUND: Lumbar disc herniation (LDH) can affect lower limb muscle function resulting in an abnormal gait. This study aims to use surface electromyography (SEMG) to evaluate patients with L4/L5 and L5/S1 LDH throughout muscle movement. METHODS: Twenty L4/L5 LDH patients (L5 Group), twenty L5/S1 LDH patients (S1 Group), and twenty healthy controls (Healthy) were recruited for the study. SEMG of bilateral tibialis anterior (TA) and lateral gastrocnemius (LG) muscles of patients were recorded using the DELSYS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 34 publications
1
14
0
Order By: Relevance
“…Cosamalón-Gan et al [ 12 ] found that there is a close relationship between the generation of lumbar disc herniation and inflammatory response and mechanical compression; the pulp nucleus in the herniated disc compresses the nearby healthy tissue, resulting in an ischemic state of the nerve root, in addition to annulus fibrosus rupture causing chemical irritation, causing an immune response and aggravating the degree of nerve root inflammation. Moreover, the protrusion produces traction and compression effects on the nerve roots, resulting in blockage of local venous blood return, aggravating the degree of nerve root edema, impaired lumbar function, and increased sensitivity to pain, so when treating, attention should be paid to the relief of the degree of pain and improving its lumbar function [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Cosamalón-Gan et al [ 12 ] found that there is a close relationship between the generation of lumbar disc herniation and inflammatory response and mechanical compression; the pulp nucleus in the herniated disc compresses the nearby healthy tissue, resulting in an ischemic state of the nerve root, in addition to annulus fibrosus rupture causing chemical irritation, causing an immune response and aggravating the degree of nerve root inflammation. Moreover, the protrusion produces traction and compression effects on the nerve roots, resulting in blockage of local venous blood return, aggravating the degree of nerve root edema, impaired lumbar function, and increased sensitivity to pain, so when treating, attention should be paid to the relief of the degree of pain and improving its lumbar function [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our findings are consistent with those of previous studies showing greater co-contraction between antagonistic muscles around the lumbar region of LDH patients and in the lower limb of older adults; additionally, this observation is extended to the lower limb muscles of LDH patients during walking 3,19 . The TA-LG co-contraction increased in LDH patients as an inefficient muscular coordination strategy, which can compensate for pain, numbness, stability, and proprioception caused by prolonged muscle co-contraction or disordered timing of muscle activation in the TA and LG during walking 5,26 . The decreased RF-BL co-contraction in the contralateral side of LDH patients compared with the healthy group could be associated with the increased amplitude of BL activities.…”
Section: Discussionmentioning
confidence: 99%
“…During this period, there were 154 patients with LDH, excluding 29 patients who were not suitable for hot compress treatment, 25 patients who were unwilling to accept the test, 2 patients with traditional Chinese medicine allergy, 6 patients who changed to surgery due to aggravation of pain, and the other 92 patients signed informed consent. A total of 13 cases were included in the study due to different reasons [ 18 , 19 ]. A total of 26 patients received simple sandbag hot compress, 26 patients received simple traditional Chinese medicine hot compress, and 27 patients received traditional Chinese medicine sandbag hot compress.…”
Section: Methodsmentioning
confidence: 99%